Judges for British Subjects in Spanish East Florida - M.C. Mirow (Washington University Journal of Law & Policy, 2021)
In 1784, the sovereignty of St. Augustine and East Florida was transferred to Spain. This study will address several aspects of Zéspedes’s reestablishment of Spanish sovereignty in East Florida. First, it presents the general structure of his government with a particular focus on legal institutions and derecho indiano. Second, it discusses Zéspedes’s legal solutions to Spanish rule in the context of a persistent British population in East Florida during the transition. These solutions included judges for British subjects and ad hoc proclamations from the governor in the absence of comprehensive instructions from the king.
Keywords: East Florida; judge; judges; sovereignty; Spain; Spanish; Great Britain; British; Zespedes; derecho indiano